MODELS USED TO ENHANCE THE QUALITY OF CLINICAL PRACTICE EVALUATION AMONG NURSING STUDENTS: A SYSTEMATIC REVIEW - Saputra, Muhamad Andika Sasmita; Sansuwito, Tukimin bin; Said, Faridah Mohd (Citra Internasional Institute, 2024)
Background: Clinical practice evaluation in nursing education is crucial to ensuring students have the competencies for optimal nursing practice, aligning with WHO standards. However, data from NCSBN indicates a significant need for more effective and comprehensive evaluation models. Aim: This aims to do a systematic review to identify and analyse evaluation models used in nursing education to enhance the quality of clinical practice evaluation for students, as well as strengths and weaknesses. Methodology: This systematic review was conducted by searching electronic database sources through journal search engines such as Google Scholar, ProQuest, CINAHL, PubMed, and Science Direct. The inclusion criteria were open-access journals published within the last five years (2018-2023). A journal search used key terms